A performance analysis of profit determination using ratio analysis: A case of Bank Islam Malaysia Berhad / Noraini Ismail - Ismail, Noraini (2011)
The study evaluates the profit performance of Islamic bank (Bank Islam Malaysia Berhad (BIMB) in terms of profitability ratio analysis such as Return on Asset, Return on Equity and also Net Profit Margin for the period 1990 until 2009. Financial ratios are applied in measuring these performances. T-test and F-test are used in determining their significance. The findings of this study will be beneficial to Bank Islam Malaysia Berhad in recognizing the factors that determine the profit performance. This uses secondary data and data analysis to shows the relationship between the profit and ROA, ROE and NPM and the factor that highly influence the profit performance. Finally, the findings indicate that two independent variables have significant relationship towards dependent variable which is the ROA and NPM have significant relationship with profit performance